2022
DOI: 10.1155/2022/6595989
|View full text |Cite|
|
Sign up to set email alerts
|

Distinctive Metabolism-Associated Gene Clusters That Are Also Prognostic in Intrahepatic Cholangiocarcinoma and Hepatocellular Carcinoma

Abstract: Objective. To offer new prognostic evaluations by exploring potentially distinctive genetic features of hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC). Methods. There were 12 samples for gene expression profiling processes in this study. These included three HCC lesion samples and their matched adjacent nontumor liver tissues obtained from patients with HCC, as well as three ICC samples and their controls collected similarly. In addition to the expression matrix generated on our own, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…CYP2C9 is a member of the cytochrome P2C (CYP2C) family and is involved in clinical drug metabolism. The low expression of CYP2C9 and LCAT in HCC is associated with poor prognosis [20][21][22]. Nevertheless, the research on the expression of CENPE in HCC samples and its clinical relevance is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C9 is a member of the cytochrome P2C (CYP2C) family and is involved in clinical drug metabolism. The low expression of CYP2C9 and LCAT in HCC is associated with poor prognosis [20][21][22]. Nevertheless, the research on the expression of CENPE in HCC samples and its clinical relevance is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established that etiologies such as ALD and cirrhosis have isoform specificities in their impact on CYP metabolism ( Marino et al, 1998 ; Yang et al, 2003 ) with CYP2C and CYP2D being the most altered between healthy controls and liver disease cohorts ( Frye et al, 2006 ). In HCC, Cyp enzymes responsible for PUFA metabolism have been identified among the top genes enriched in a study aimed at elucidating prognostic markers ( Ding et al, 2022 ). This study also identified CYP26A1, CYP2C9 and CYP4F2 among a proposed prognostic panel of genes when trying to model the risks for iCCA and HCC ( Ding et al, 2022 ).…”
Section: Biological Functions Of Oxylipins In Liver Disease and Cance...mentioning
confidence: 99%
“…In HCC, Cyp enzymes responsible for PUFA metabolism have been identified among the top genes enriched in a study aimed at elucidating prognostic markers ( Ding et al, 2022 ). This study also identified CYP26A1, CYP2C9 and CYP4F2 among a proposed prognostic panel of genes when trying to model the risks for iCCA and HCC ( Ding et al, 2022 ). In a separate cohort, the expression of CYP2A6 was also closely associated with tumor grades and favorable prognosis ( Jiang et al, 2021 ).…”
Section: Biological Functions Of Oxylipins In Liver Disease and Cance...mentioning
confidence: 99%
“…A variety of liver-specific genes (LSGs) were presented to be associated with HCC development and progression. For instance, RDH16 was shown to be downregulated in HCC and associated with HCC survival [ 14 , 15 ]. Inverse association of SLC10A1 with HCC occurrence and progression were reported [ 16 ].…”
Section: Introductionmentioning
confidence: 99%